I need to decide wether the following is true (and, of course, justify it): given $V = [v_1, v_2, ..., v_n]$, $v$, $w$ in $V$ and $<v,v_i> = <w,v_i>$, for any $i$, so $v = w$.

I wrote the following: if $v$ is in V, we have $ v = \alpha_1v1 + \alpha_2v_2 + \dots + \alpha_nv_n$. The same holds for $w$: $w = \beta_1v_1 + \beta_2v_2 + \dots + \beta_nv_n$. Now $<v,v_i> = <\alpha_1v1 + \alpha_2v_2 + \dots + \alpha_nv_n, v_i>$ and $<w,v_i> = <\beta_1v_1 + \beta_2v_2 + \dots + \beta_nv_n, v_i>$.

But $<v,v_i> = <\alpha_1v1 + \alpha_2v_2 + \dots + \alpha_nv_n, v_i> = \alpha_1<v_1,v_i> + \alpha_2<v_2,v_i> + \dots + \alpha_n<v_n,v_i>$ due to linearity property of the internal product. Also, $<w,v_i> = <\beta_1v1 + \beta_2v_2 + \dots + \beta_nv_n, v_i> = \beta_1<v_1,v_i> + \beta_2<v_2,v_i> + \dots + \beta_n<v_n,v_i>$.

The only way we can have $<v,v_i> = <w,v_i>$ is if $\alpha_j = \beta_j, j = 1, \dots, n$. But if $\alpha_j = \beta_j, j = 1, \dots, n$ implies $v=w$ because they are from the same span.

Is this correct? Is it enough to justify? The proof would still hold if nothing was said about $v$ and $w$ in $V$?

  • $\begingroup$ What are the properties of $V$, because depending on them, this could be true or false. $\endgroup$ – Don Thousand Aug 20 '18 at 22:13
  • $\begingroup$ V is a vector space with an inner product. That's the only other info given. $\endgroup$ – daniel.franzini Aug 20 '18 at 22:18
  • $\begingroup$ Please try to make the titles of your questions more informative. For example, Why does $a<b$ imply $a+c<b+c$? is much more useful for other users than A question about inequality. From How can I ask a good question?: Make your title as descriptive as possible. In many cases one can actually phrase the title as the question, at least in such a way so as to be comprehensible to an expert reader. You can find more tips for choosing a good title here. $\endgroup$ – Shaun Aug 20 '18 at 22:30
  • $\begingroup$ Fixed. Thank you. $\endgroup$ – daniel.franzini Aug 20 '18 at 22:35

This is correct.

Another way would be to suppose $v\neq w$. Then $v-w\neq0$ so that $$ \left\langle v-w, v-w\right\rangle =\left\lVert v-w\right\rVert^2 >0 $$ On the other hand, the nonzero vector $v-w$ is guaranteed to be a vector in a basis, so $$ \left\langle v-w, v-w\right\rangle = \langle v, v-w\rangle-\langle w, v-w\rangle = \langle v, v-w\rangle-\langle v, v-w\rangle = 0 $$ This contradiction implies that $v=w$.


Here's how I would show it

Let $v,w\in V$ be expressed as linear combinations of the basis vectors of $V$. Since we assume $v\neq w$, $\exists b_i\in B$, the basis, such that in the linear combination, the coefficient of $b_i$ for $v$, which we call $v_{bi}$, is different from the coefficient of $b_i$ in $w$'s linear combination, denoted by $w_{bi}$.

Hence, $v\cdot b_i=v_{bi}$ and $w\cdot b_i=w_{bi}$, so $<v,v_i> \neq <w,v_i>$ for all $v_i$. We have proved the contrapositive, so we are done.


I guess you essentially have it... Here's my try:

For some $k\le n$, $\{v_{i_1},\dots, v_{i_k}\}\subset\{v_1,\dots, v_n\}$ is a basis for $V$.

Apply the hypothesis to get that $v$ and $w$ have the same components relative to this basis. Specifically, $\frac{\langle v,v_{i_j}\rangle}{\mid v_{i_j}\mid^2}=\frac{\langle w,v_{i_j}\rangle}{\mid v_{i_j}\mid^2}$ is the $j$th component of both $v$ and $w$, $j=1,\dots, k$. That proves $v=w$.

  • $\begingroup$ The hypothesis only says that $<v,v_i> = <w,v_i>$. I fail to see why the components are equal because nothing was said about the norm of $v_i$. $\endgroup$ – daniel.franzini Aug 22 '18 at 20:59
  • $\begingroup$ The norm of $v_i$ is the same on both sides, so I think it's alright... $\endgroup$ – Chris Custer Aug 22 '18 at 23:31
  • $\begingroup$ You are right, sorry. $\endgroup$ – daniel.franzini Aug 24 '18 at 18:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.